Podcast como recurso multimedia para el proceso de aprendizaje en el área de lengua y literatura. - Vallejo Pilco, Josué Alejandro (2025)
The present research project focuses on the creation of podcasts as a multimedia resource in the teaching of Language and Literature. The podcast is proposed as an accessible and dynamic tool that enhances listening comprehension and autonomous learning through platforms like SoundCloud, facilitating access to this type of content and allowing students to reinforce knowledge outside the classroom in a flexible and engaging way. The theoretical framework grounds the research in various learning theories, such as constructivism, connectivism, and Vygotsky’s sociocultural theory, which support the importance of educational technology in the learning process. Pedagogical approaches are also addressed, highlighting the communicative approach and project-based learning, both of which promote active student engagement. The Kanban methodology is used to optimize the organization of planning, pre-production, production, and post-production involved in the podcast creation process. The target population for this research includes students and teachers in upper basic education in the area of Language and Literature. It is recommended to carry out ongoing analysis of the podcast’s reach and acceptance on the platform, using tools to measure the number of plays and comments. Another important consideration is to explore distribution on other digital platforms to expand the audience beyond the educational environment, such as Spotify or Google Podcasts.